The Effect of ZSM-5 Zeolite and Dolomite Catalysts on the Performance of Plastic Waste Pyrolysis - Tampubolon, Adam Jordan; Gamayel, Adhes; Zaenudin, Mohamad (Jakarta Global University, 2023)
The increasing volume of waste in Indonesia, particularly plastic waste, has led to significant environmental challenges due to its continuous accumulation. Pyrolysis offers a sustainable alternative to conventional disposal methods, such as landfilling and incineration, which are known to contribute to pollution. Pyrolysis is a thermochemical decomposition process carried out in an oxygen-deficient environment, converting plastic waste into valuable products, including gas, oil, and char. These products have various applications: the gas can be used as a fuel, the oil as a liquid fuel, and the char as a solid fuel. This study investigates the pyrolysis of three types of plastic feedstocks: high-density polyethylene (HDPE), polypropylene (PP), and a 50:50 mixture of HDPE and PP. The catalysts employed were ZSM-5 zeolite, dolomite, and a mixed catalyst comprising ZSM-5 zeolite and dolomite, with a catalyst-to-feedstock ratio of 0.2:1. The results revealed that the highest oil yields were achieved using the ZSM-5 zeolite catalyst, producing 243 ml from HDPE, 370 ml from PP, and 380 ml from the HDPE-PP mixture. Conversely, the dolomite catalyst yielded the lowest oil production, with 82 ml from HDPE, 20 ml from PP, and 282 ml from the HDPE-PP mixture. Additionally, the ZSM-5 zeolite catalyst demonstrated a consistent increase in the oil production rate every 10 minutes across all feedstocks. These findings highlight the effectiveness of ZSM-5 zeolite in enhancing oil yield during pyrolysis, offering a viable pathway for converting plastic waste into valuable energy resources.